Formal Methods for Open Object-Based Distributed Systems - Barthe, Gilles (Springer, 2017)
This book constitutes the refereed proceedings of the 10th IFIP WG 6.1 International Conference on Formal Methods for Open Object-Based Distributed Systems, FMOODS 2008, held in Oslo, Norway, in June 2008.